Improving Capital Regulations on Financial Institutions to Reflect Group-wide Risks - Keeyoung Rhee (Korea Development Institute (KDI), 2017)
- The group-wide risks associated with business group affiliation must be reflected in capital regulations that assess the soundness of financial institutions. - When financial institutions hold shares with the intent to maintain control over a business group, the insolvency of one affiliate could rapidly spread throughout the entire group due to difficulties in disposing of the respective shares. - If such risks are not reflected in capital regulations, the capital adequacy of financial institutions [in groups] against losses may be assessed inaccurately. - It was found that the current capital regulations on insurance and securities companies do not reflect the group-wide risks posed by affiliates?? investments in shares. - The risks may be underestimated for capital regulations on insurance companies as the companies?? investments in non-consolidated affiliates are regarded as general stock investments. - As for capital regulations on securities companies, capital adequacy may be incorrectly assessed due to the deduction of the whole investment in affiliates from their capital.
Keywords: 330